The Use of Oral Analgesics and Pain Self-Efficacy Are Independent Predictors of the Quality of Life of Individuals with Rheumatoid Arthritis - Akira Hashimoto; Motoki Sonohata; Masaaki Mawatari (Pain Research and Management)
Objectives. This study investigated the relationship between quality of life (QOL) and several factors, including pain assessments, in patients with rheumatoid arthritis (RA). Methods. This cross-sectional, single-center study enrolled 85 patients with RA. The variables investigated included demographic characteristics, the 28-joint disease activity score with C-reactive protein (DAS28-CRP), painDETECT questionnaire (PDQ), pain self-efficacy questionnaire (PSEQ), and pain catastrophizing scale (PCS). QOL was measured using the Japanese validated version of the European Quality of Life questionnaire with five dimensions and five levels (EQ-5D-5L). Results. The use of oral steroids and oral analgesics was significantly associated with low EQ-5D-5L scores (P<0.05). EQ-5D-5L score had a significant positive association with PSEQ (r = 0.414) and significant negative association with age, disease duration, DAS28-CRP, PDQ, and PCS (r = −0.217, −0.343, −0.217, −0.277, and −0.384, respectively). Multiple regression analysis showed that the use of oral analgesics and PSEQ were independent predictors of EQ-5D-5L score (β = -0.248, P<0.05 and β = 0.233, P<0.05). Conclusions. The use of oral analgesics by RA patients may influence their QOL, which, in turn, may affect their feelings of self-efficacy. Various pain management strategies, including surgical treatment, may be explored for the treatment of RA. Furthermore, the PSEQ may be a prominent part of the patient’s overall assessment.